Persepsi Mahasiswa Terhadap Perkuliahan dalam Jaringan (Daring) pada Mata Kuliah Matematika 2 - Wiga Ariani; Delpima Suhita; Nur Hikmah (Journal on Education, 2022)
The purpose of this research was to look at the tendency of students' perceptions of online learning in mathematics 2. This research is a quantitative research with survey method. The main data source of this research was obtained from the respondents. This research was carried out at Mechanical Engineering Study Program, faculty of engineering, Krisnadwipaya University, in June 2022. Data collection techniques using questionnaires. Respondent in this research were student of the 2nd semester of mechanical engineering study program in the 2021-2022 academic year. The measurement scale used is a Likert scale with a scale of strongly agree (SS), agree (s), disagree (TS), strongly disagree (STS). The data analysis technique used descriptive statistics. The average percentage of 76.08% for the aspect of online lecture facilities and infrastructure located in the area strongly agrees that the facilities and infrastructure are very supportive of carrying out online lectures. The percentage of 78.57% which is located in the regions strongly agrees with the online lecture aspect in the mathematics course 2. This means that online learning activities can run well and according to the RPS and have a positive impact on students in terms of critical thinking, innovation, expressing communication ideas, and utilization. technology.